2001
DOI: 10.1002/dvdy.1127
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sites of L‐histidine decarboxylase expression in mouse suggest novel developmental functions for histamine

Abstract: Histamine mediates many types of physiologic signals in multicellular organisms. To clarify the developmental role of histamine, we have examined the developmental expression of L-histidine decarboxylase (HDC) mRNA and the production of histamine during mouse development. The predominant expression of HDC in mouse development was seen in mast cells. The HDC expression was evident from embryonal day 13 (Ed13) until birth, and the mast cells were seen in most peripheral tissues. Several novel sites with a promin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 65 publications
5
31
0
Order By: Relevance
“…Although further studies are needed to elucidate the functions of histamine, HDC and H 1 R in the physiology of ES cells, these results support the observation that histamine may affect differentiation of certain cell lineages [8]. …”
Section: Resultssupporting
confidence: 73%
“…Although further studies are needed to elucidate the functions of histamine, HDC and H 1 R in the physiology of ES cells, these results support the observation that histamine may affect differentiation of certain cell lineages [8]. …”
Section: Resultssupporting
confidence: 73%
“…During embryonic development, HDC is expressed in a variety of tissues, including the brain, sensory neurons of the OE, pharyngeal organ, and mast cells (Karlstedt et al, 2001). There are locations where we detected MAOB during development (Table 1).…”
Section: Maob Expression In the Histaminesynthetizing Populationsmentioning
confidence: 89%
“…(38) There is also evidence of differential HDC expression depending on the differentiation/developmental stage. (6,39) Zhao and coworkers have reported that HDC can also be regulated at translational level in an important extent. (21) This work also claims the finding of a histamine auto-feedback inhibition on HDC in enterochromaffin-like cells.…”
Section: Introductionmentioning
confidence: 97%